Pengaruh Radiasi Plasma Lucutan Pijar Korona dan Pupuk Organik Rumen Sapi terhadap Produksi Bayam Cabut (Amaranthus tricolor L.) - Ulfi Nadzifah; Erma Prihasanti; Sumariyah Sumariyah (Jurnal Biologi Papua, 2020)
This study aims to determine the effect of radiation of corona glow discharge plasma and rumen organic fertilizer to the productivity of spinach (Amaranthus tricolor L). The study was conducted using factorial Completely Randomized Design 3 x 4 consisting of 12 treatments and 6 replications with plasma radiation treatment factors and additions of rumen organic fertilizer. Plasma radiation is carried out with a duration of 0 minutes, 25 minutes, 35 minutes, and 45 minutes, while the additions of cow rumen organic fertilizer is 0 g, 25 g, and 50 g per plant. Parameters observed included root length, stem length, number of leaves, wet weight, dry weight, and chlorophyll content. Data obtained from the research results were analyzed using ANOVA test and DMRT further test. The results showed that there was an interaction of radiation of c corona glow discharge and additions of cattle rumen organic fertilizer to stem length, wet weight, and plant dry weight, but there was no interaction between both root length, leaf number, and total chlorophyll content of spinach plants. The interaction of the two treatment factors showed significant results in 45 minutes of radiation treatment and the addition of 50 organic fertilizer. The treatment increased root length by 258%, stem length 240%, leaf number 84%, wet weight 1587%, dry weight 1275% compared to control treatment. The results of this study concluded that radiation of corona glow discharge and rumen organic fertilizer affected the productivity of spinach spinach (Amaranthus tricolor L.).